2021
DOI: 10.1093/intimm/dxab099
|View full text |Cite
|
Sign up to set email alerts
|

DNAM-1 promotes inflammation-driven tumor development via enhancing IFN-γ production

Abstract: DNAM-1 is an activating immunoreceptor on T cells and natural killer (NK) cells. Expression levels of its ligands, CD155 and CD112, are upregulated on tumor cells. The interaction of DNAM-1 on CD8 + T cells and NK cells with the ligands on tumor cells plays an important role in tumor immunity. We previously reported that mice deficient in DNAM-1 showed accelerated growth of tumors induced by the chemical carcinogen 7,12-dimethylbenz[a]anthracene (DMBA). Contrary to those results, we show here that tumor develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…Our results show that EV71 infection interferes the TLR4 signaling pathway by inhibiting the MYD88 activation and downstream NF-κB phosphorylation. Furthermore, studies have shown that EV71 infection can suppress the production of various inflammatory factors, such as IL-6 ( Tanaka et al., 2014 ), NLRP3 ( Zhang et al., 2023 ), COX2 ( Gupta et al., 2018 ) and IFN-γ ( Nakamura-Shinya et al., 2022 ), thereby dampening the immune response and these findings are consistent with our results. In addition, we find that EV71 infection also inhibits the p-TBK1/TBK1 protein level to suppress the antiviral innate immune response.…”
Section: Discussionsupporting
confidence: 92%
“…Our results show that EV71 infection interferes the TLR4 signaling pathway by inhibiting the MYD88 activation and downstream NF-κB phosphorylation. Furthermore, studies have shown that EV71 infection can suppress the production of various inflammatory factors, such as IL-6 ( Tanaka et al., 2014 ), NLRP3 ( Zhang et al., 2023 ), COX2 ( Gupta et al., 2018 ) and IFN-γ ( Nakamura-Shinya et al., 2022 ), thereby dampening the immune response and these findings are consistent with our results. In addition, we find that EV71 infection also inhibits the p-TBK1/TBK1 protein level to suppress the antiviral innate immune response.…”
Section: Discussionsupporting
confidence: 92%